Hepatitis C‐induced hepatocyte apoptosis following liver transplantation is enhanced by immunosuppressive agents. Issue 9 (11th May 2016) - Lim, E. J.; Chin, R.; Nachbur, U.; Silke, J.; Jia, Z.; Angus, P. W.; Torresi, J.
Summary: In recurrent hepatitis C (HCV) post‐liver transplantation (OLT), the combination of immunosuppressants and HCV is postulated to increase hepatocyte apoptosis and liver fibrosis. We evaluated hepatocyte apoptosis within the liver tissue of patients with postOLT HCV recurrence compared to HCV‐negative individuals and correlated these findings with the effects of immunosuppressants on HCV‐induced cell death and its inhibition in primary mouse hepatocytes (PMoH). Liver biopsies from patients with and without HCV were evaluated by immunohistochemistry for markers of apoptosis M30 CytoDEATH (M30) and cleaved PARP (clPARP). PMoH from C57BL/6 mice were infected with recombinant adenoviruses (rAdHCV) that expressed HCV proteins in hepatocytes. Infected cells were treated with cyclosporine, tacrolimus, sirolimus and/or MMF with or without pan‐caspase inhibitor Q‐VD‐Oph. Cell viability and apoptosis were evaluated using crystal violet assays and Western immunoblots probed for cleaved caspase‐3 (clCas3) and clPARP. Both M30 and clPARP were increased in the liver biopsies of patients with postOLT HCV recurrence compared to HCV‐negative individuals. Treatment of rAdHCV‐infected PMoH with cyclosporine, tacrolimus or sirolimus reduced cell viability and increased clCas3 and clPARP compared to rAdHCV infection alone. Addition of MMF to cyclosporine, tacrolimus or sirolimus further reduced cell viability and increased clCas3 and clPARP. Q‐VD‐Oph improved cell viability in HCV‐infected PMoH treated with immunosuppressants alone and in combination and reduced clCas3 and clPARP by approximately 90%. Immunosuppressive agents, especially in combination, enhanced apoptosis in HCV‐infected hepatocytes. The finding that Q‐VD‐Oph reversed hepatocyte death suggests that treatments utilizing apoptosis inhibition might reduce liver injury in postOLT HCV recurrence.